Efeito da percolação de biodiesel na condutividade hidráulica de geocomposto bentonítico - Favretto, Julia (2023)
The use of Geosynthetic Clay Liners (GCLs) as a contaminant containment barrier is an efficient alternative to protect natural soil and groundwater and surface water. GCL is capable of containing fuel leaks in distribution centers, reservoirs and during transportation, thanks to the low hydraulic conductivity of the bentonite present in the geocomposite, when hydrated. It is important, however, to evaluate the behavior of GCL when interacting with contaminants to ensure that its hydraulic properties are not compromised and that its retention capacity is maintained. In view of the increasing insertion of biofuels in the Brazilian and global energy matrix, this study sought to evaluate the hydraulic behavior of a GCL permeated with biodiesel. To this end, a bibliometric study related to the hydraulic behavior of GCLs in contact with fuels was initially carried out. The experimental program evaluated the effects on the hydraulic conductivity of GCL of pre-hydration and saturation of the material, both with water and with the contaminant under study, as well as of hydration and dehydration cycles. Additionally, complementary expansion tests were performed on the bentonite in contact with the two liquids. The hydraulic conductivity tests were conducted in the laboratory, using a flexible wall, whose construction and validation were part of this research. The reference values ​​of hydraulic conductivity of the GCL for percolation with water were met, validating the permeameter and making it suitable for carrying out the planned tests. The average hydraulic conductivity of the geocomposite, when hydrated and permeated with water, was 4.9 x 10-11 m/s. For the samples hydrated with water and permeated with biodiesel, the value was 9.9 x 10-11 m/s, indicating an increase of approximately 2 times for the flow with contaminant. It was also observed that the prior hydration and saturation of the GCL with water before percolation with biodiesel is essential due to the non-expansive behavior of the bentonite in contact with the organic compound. The average value of hydraulic conductivity of the GCL pre-hydrated with biodiesel was approximately 30 times higher than when pre-hydrated with water. Regarding the tests with samples subjected to previous wetting and drying cycles, an approximate 3.5-fold increase in hydraulic conductivity was observed for samples exposed to 40 cycles compared to those exposed to 10 cycles. The results demonstrate the efficiency of GCL as a biodiesel containment barrier and highlight the need for adequate hydration of the material before its exposure to the contaminant, as well as the importance of considering the humidity variations to which it may be subjected during operation.